The New Marketing : How to Win in the Digital Age - Burgess, Cheryl (SAGE Publications, Ltd. (UK), 2020)
In our hyper-connected world that is changing at warp speed, marketers recognize the need to shift from traditional marketing methods to a new way that can help them better navigate the unpredictable environment. For traditionalists, this change has posed a challenge. Many have tried to incorporate new approaches into the old models they grew up with, only to be frustrated with the results.  From the bestselling authors of The Social Employee, and LinkedIn Learning course authors, comes a powerful new textbook that cracks the marketing code in our hyper-focused digital age.    The New Marketing, with contributions spanning CMO trailblazers to martech disruptors, behavioral economics luminaries at Yale to leading marketing thinkers at Kellogg and Wharton, is a GPS for navigating in a digital world and moves the craft of marketing through the forces of marketing transformation.  We can’t predict the future. But our goal is to help make Masters/MBA students and marketing practitioners future-ready and successful.